Community empowerment model in mining areas to improve welfare: Some lessons from Jambi Province, Indonesia - Haryadi, Haryadi; Nurhayani, Nurhayani; Achmad, Erni; Rosmeli, Rosmeli (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
Jambi Province holds significant potential in the coal mining sector, contributing substantially to Local Own Source Revenue and supporting the local economy. With the sixth-largest coal reserves in Indonesia, these resources are spread across key districts such as Sarolangun, Muaro Jambi, Tebo, Batanghari, and Bungo. The coal mining sector provides economic benefits not only through job creation and infrastructure development but also poses significant social and environmental challenges, including air pollution, road damage, and degradation of water quality. This study aims to (1) analyze the social, economic, and environmental impacts of coal mining activities in Jambi Province, (2) evaluate the effectiveness of empowerment programs implemented by companies through CSR, and (3) design an empowerment model that can improve the welfare and economic independence of communities surrounding the mines. The research methodology includes field surveys, SWOT analysis, and Analytical Hierarchy Process (AHP) to determine program priorities. The findings reveal that CSR activities around the mines have a positive impact on community welfare; however, challenges exist in program sustainability and limited community involvement in planning. The SWOT analysis identifies strengths, weaknesses, opportunities, and threats, such as community dependence on the mining sector and significant environmental impacts. Based on the AHP results, the priority programs identified include skills training, support for small and medium-sized enterprises (SMEs), and the enhancement of educational and healthcare infrastructure to create a sustainable impact. To maximize the economic benefits of mining, a community empowerment model that focuses on economic diversification and community engagement is necessary. This study recommends collaboration between companies and the government to develop inclusive and sustainable programs that improve the welfare of communities surrounding mining areas.